Effects of the PPAR alpha agonist WY-14,643 on plasma lipids, enzymatic activities and mRNA expression of lipid metabolism genes in a marine flatfish, Scophthalmus maximus - Urbatzka, R.
Fibrates and other lipid regulator drugs are widespread in the aquatic environment including estuaries and coastal zones, but little is known on their chronic effects on non-target organisms as marine fish. In the present study, turbot juveniles were exposed to the PPAR model agonist WY-14,643 for 21 days by repeated injections at the concentrations of 5 mg/kg (lo-WY) and 50 mg/kg (hi-WY), and samples taken after 7 and 21 days. Enzyme activity and mRNA expression of palmitoyl-CoA oxidase and catalase in the liver were analyzed as first response, which validated the experiment by demonstrating interactions with the peroxisomal fatty acid oxidation and oxidative stress pathways in the hi-WY treatment. In order to get mechanistic insights, alterations of plasma lipids (free cholesterol, FC; HDL associated cholesterol, C-HDL; triglycerides, TG; non-esterified fatty acids, NEFA) and hepatic mRNA expression of 17 genes involved in fatty acid and lipid metabolism were studied. The exposure to hi-WY reduced the quantity of plasma FC, C-HDL, and NEFA. Microsomal triglyceride transfer protein and apolipoprotein E mRNA expression were higher in hi-WY, and indicated an increased formation of VLDL particles and energy mobilization from liver. It is speculated that energy depletion by PPAR agonists may contribute to a higher susceptibility to environmental stressors.